Generalized Elastic Lateral-Torsional Buckling of Steel Beams - Glauz, Robert S.; Schafer, Benjamin W. (Engineering Journal, 2026)
Errata to Vol. 62, No. 1 paper Generalized Elastic Lateral-Torsional Buckling of Steel Beams